2020
DOI: 10.1002/jcp.29923
|View full text |Cite
|
Sign up to set email alerts
|

Excavating SARS‐coronavirus 2 genome for epitope‐based subunit vaccine synthesis using immunoinformatics approach

Abstract: Since the outbreak of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) in December 2019 in China, there has been an upsurge in the number of deaths and infected individuals throughout the world, thereby leading to the World Health Organization declaration of a pandemic. Since no specific therapy is currently available for the same, the present study was aimed to explore the SARS-CoV-2 genome for the identification of immunogenic regions using immunoinformatics approach. A series of computational to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…In the present study we have proposed a non allergenic and non toxic vaccine construct with acceptable physiological properties, which is composed of highly immunogenic B and T cell epitopes from two structural and three non-structural proteins of SARS-CoV-2. In comparison to our study with other similar reports where both classes of proteins have been utilized (Ahmad et al, 2020 ; Chauhan et al, 2021 ; Enayatkhani et al, 2021 ; Srivastava et al, 2020 ), we found that our proposed candidate exhibits enhanced immunogenic potential on account of its predicted antigenicity score. Moreover, the combinations of proteins/epitopes that we have utilized have not been explored by any other immunoinformatics study so far.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In the present study we have proposed a non allergenic and non toxic vaccine construct with acceptable physiological properties, which is composed of highly immunogenic B and T cell epitopes from two structural and three non-structural proteins of SARS-CoV-2. In comparison to our study with other similar reports where both classes of proteins have been utilized (Ahmad et al, 2020 ; Chauhan et al, 2021 ; Enayatkhani et al, 2021 ; Srivastava et al, 2020 ), we found that our proposed candidate exhibits enhanced immunogenic potential on account of its predicted antigenicity score. Moreover, the combinations of proteins/epitopes that we have utilized have not been explored by any other immunoinformatics study so far.…”
Section: Discussionsupporting
confidence: 73%
“…Several groups have utilized this approach in developing candidate vaccines to combat Covid-19. Most of these immunoinformatics studies have focussed on prediction of epitopes from a single protein, majorly the surface spike glycoprotein (Abraham Peele et al, 2020 ; Bhatnager et al, 2020 ; Bhattacharya et al, 2020 ; Kar et al, 2020 ; Naz et al, 2020 ; Rahman et al, 2020 ; Samad et al, 2020 ; Sanami et al, 2020 ) or a single category of proteins, either structural or non-structural (Kalita et al, 2020 ; Ojha et al, 2020 ; Sarkar & Ullah, 2020 ); relatively few are focused on a candidate that utilizes both these classes of proteins (Ahmad et al, 2020 ; Chauhan et al, 2021 ; Enayatkhani et al, 2021 ; Srivastava et al, 2020 ; Tahir et al, 2020 ).Some others have employed only CTL epitopes leaving the significant B-cell or HTL epitopes (Mishra, 2020 ). In the present study we have proposed a non allergenic and non toxic vaccine construct with acceptable physiological properties, which is composed of highly immunogenic B and T cell epitopes from two structural and three non-structural proteins of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…The B-cells mediate the humoral immune response by producing antibodies and keeping the memory of a previous infection. However, the humoral immune response provided by the B-cells may get weaker overtime and pathogens or antigens can easily overcome the humoral immune response [ 124 ]. In such cases, the cell-mediated immune response can provide much broader, often life-long immunity by secreting antiviral cytokines and specifically identifying and destroying the infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…By combining all of the possible CTL, HTL, and LBL epitopes with suitable adjuvant and flexible linkers, a multi-epitope vaccine was constructed [ 62 , 63 ]. Based on the immunological filters mentioned above, the best potential epitopes were screened and combined to produce a single peptide chain [ 64 ]. Because peptides are not immunogenic on their own, an adjuvant is necessary to stimulate the immune response [ 65 , 66 ].…”
Section: Methodsmentioning
confidence: 99%